Competition and well-being - Jordi Brandts; Arno Riedl; Frans van Winden (Institute for the Study of Labor (IZA), 2005)
This paper experimentally studies the effects of competition in an environment where people's actions can not be contractually fixed. We find that, in comparison with no competition, the presence of competition does neither increase efficiency nor does it yield any gains in earnings for the short side of the exchange relation. Moreover, competition has a clearly negative impact on the disposition towards others and on the experienced well-being of those on the long side. Since subjective well-being improves only for those on the short side competition contributes to larger inequalities in experienced well-being. All in all competition does not show up as a positive force in our environment.
Keywords: A13; C92; D30; J50; M50; 330; competition; happiness; well-being; laboratory experiment; emotions; market interaction; Wettbewerb; Unvollständiger Vertrag; Lebensqualität